Pengaruh Suhu dan Lama Pengeringan Terhadap Karakteristik Teh Herbal Matcha Daun Tenggulun (Protium javanicum Burm.F.) - Mei Sarah Purba, Yohanna; Yusasrini, Ni Luh Ari; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
The purpose of this research were to determine the temperature and duration of dried time on characteristics of the matcha herbal tenggulun leaves tea, as well as to determine the appropriate temperature and dried time to produce matcha herbal tenggulun leaves tea with the best characteristics. Experimental design that used on this research was Completely Randomized Design (CRD) with factorial pattern. This research was repeated 2 times so obtained 18 trial units. The parameters observed in this research were : water content, the total amount of flavonoid, fenol, and tannin, antioxidants activity based on IC50, The result of this research showed that temperature and drying time of tenggulun leaf matcha herbal tea had a significant effect on water content, the total amount of flavonoid, fenol, tannin, and antioxidants activity based on IC50 and affects of color, aroma, and overall acceptance.The best characteristic matcha herbal tenggulun leaves tea resulted from dried process at 60 o C for 120 minutes with the total amount of flavonoid 0.64 mg QE/g, total amount of fenol 9.61 mg GAE/g, total amount of tannin 4.52mg TAE/g, and antioxidants activity based on IC501253.99 ppm, green color, somewhat preferred aroma, and overall acceptance liked.